2021
DOI: 10.1111/php.13378
|View full text |Cite
|
Sign up to set email alerts
|

Binding Expedient of 2‐carbamido‐1,3‐indandione to Nucleic Acids: Potential Fluorescent Probe

Abstract: Fluorescent and computational methods were used to elucidate the binding expedient of 2‐carbamido‐1,3‐indandione (CAID) tautomers to nucleotides. The dependence of the fluorescence emission of CAID loaded nucleic acids sequences to compound concentration, temperature and time variation was investigated. It was found that the subject compound binds to nucleic acids but does not intercalate. According to our quantum‐chemical calculations on the conjugation between CAID and nucleotides, the binding in the formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Because of strong absorption in the UVA and UVB spectral region and its relatively high photostability CAID is suitable for sunscreen and as fluorescent molecular probe for investigation of different biomolecules [17]. In addition, we have shown that CAID possesses high binding affinity to DNA and RNA molecules [18], which appear to change the tautomeric equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Because of strong absorption in the UVA and UVB spectral region and its relatively high photostability CAID is suitable for sunscreen and as fluorescent molecular probe for investigation of different biomolecules [17]. In addition, we have shown that CAID possesses high binding affinity to DNA and RNA molecules [18], which appear to change the tautomeric equilibrium.…”
Section: Introductionmentioning
confidence: 99%